Contribution of Treatment with Ear Popper for Hearing in Children with Middle Ear Effusion - Ronit Priner; Ophir Ilan (MDPI AG, 2024)
Objectives: we aim to assess the contribution of the EarPopper device to hearing in children with middle ear effusion (MEE). Methods: The study has three parts, including 1. tympanometry and audiometry before and six weeks after using the EarPopper to evaluate the treatment's effect over time compared to a control group; 2. tympanometry before and immediately after using the EarPopper to evaluate immediate changes in middle ear pressure (MEP); 3. length of effect 90 min after use to assess pressure fluctuations over time. Results: Part 1 was a follow-up six weeks after using the device, and the patients in the study group that completed the study showed a significant improvement in hearing threshold. The average gain in hearing threshold ranged from 9.1 dB to 14 dB compared to the control group's max improvement of 1.1 dB. In addition, MEP was significantly improved in the study group, as most Type Bs improved to Type A and C. Part 2 was the tympanometry immediately after using EarPopper and showed the majority of Type Cs turned into Type As. The majority of Type Bs remained unchanged. Part 3 was a follow-up 90 min after use; Type Cs that had improved to Type A demonstrated a decrease in pressure and return to negative pressure. Conclusions: use of the EarPopper device for six weeks is associated with an improved hearing threshold and middle ear status.